2011
DOI: 10.1371/journal.pone.0016043
|View full text |Cite
|
Sign up to set email alerts
|

Shal/Kv4 Channels Are Required for Maintaining Excitability during Repetitive Firing and Normal Locomotion in Drosophila

Abstract: BackgroundRhythmic behaviors, such as walking and breathing, involve the coordinated activity of central pattern generators in the CNS, sensory feedback from the PNS, to motoneuron output to muscles. Unraveling the intrinsic electrical properties of these cellular components is essential to understanding this coordinated activity. Here, we examine the significance of the transient A-type K+ current (IA), encoded by the highly conserved Shal/Kv4 gene, in neuronal firing patterns and repetitive behaviors. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 60 publications
2
66
0
Order By: Relevance
“…The role of MN currents in shaping rhythmic motor activity is a subject of active research (Harris-Warrick, 2002; Heckman et al, 2009; Kiehn et al, 2000; Marder & Goaillard, 2006). Much of the recent work has focused on the role of persistent inward currents in MNs (Enríquez Denton et al, 2012; Manuel et al, 2012; Revill & Fuglevand, 2011), but outward currents have also been shown to shape MN firing during rhythmic activity (Hooper et al, 2009; Manuel et al, 2012; Ping et al, 2011; Schaefer, Worrell & Levine, 2010). In particular, a recent study in Drosophila showed that elimination of Shal -mediated currents in MNs, via expression of a dominant negative construct under the control of RRA-GAL4, altered the frequency of larval crawling (Ping et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of MN currents in shaping rhythmic motor activity is a subject of active research (Harris-Warrick, 2002; Heckman et al, 2009; Kiehn et al, 2000; Marder & Goaillard, 2006). Much of the recent work has focused on the role of persistent inward currents in MNs (Enríquez Denton et al, 2012; Manuel et al, 2012; Revill & Fuglevand, 2011), but outward currents have also been shown to shape MN firing during rhythmic activity (Hooper et al, 2009; Manuel et al, 2012; Ping et al, 2011; Schaefer, Worrell & Levine, 2010). In particular, a recent study in Drosophila showed that elimination of Shal -mediated currents in MNs, via expression of a dominant negative construct under the control of RRA-GAL4, altered the frequency of larval crawling (Ping et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the recent work has focused on the role of persistent inward currents in MNs (Enríquez Denton et al, 2012; Manuel et al, 2012; Revill & Fuglevand, 2011), but outward currents have also been shown to shape MN firing during rhythmic activity (Hooper et al, 2009; Manuel et al, 2012; Ping et al, 2011; Schaefer, Worrell & Levine, 2010). In particular, a recent study in Drosophila showed that elimination of Shal -mediated currents in MNs, via expression of a dominant negative construct under the control of RRA-GAL4, altered the frequency of larval crawling (Ping et al, 2011). The results from the RNAi experiments reported herein add to an increasing body of work suggesting that MN outward currents, and BK currents in particular, may enable MNs to shape the timing of rhythmic motor output.…”
Section: Discussionmentioning
confidence: 99%
“…Dominant negative versions of the tetrameric potassium channels Shaker, Eag, Shaw, and Shal have been made by truncation of the wild-type channels, usually after the N-terminal multimerization domain (Broughton et al, 2004;Hodge et al, 2005;Mosca et al, 2005;Ping et al, 2011). RNAi constructs against Shaw also increase neural activity (Hodge and Stanewsky, 2008).…”
Section: : Manipulation Of Neuronal Activitymentioning
confidence: 99%
“…Electrodes resistances for all perforated–patch and whole–cell recordings were 3–8 MΩ; gigaohm seals were obtained in all cases. For cell–attached recordings, electrode resistances were 7–9 MΩ, with > 5 GΩ seals; tips were fire–polished and inspected for uniform diameter. We isolated Shal currents by prepulse protocol, as previously described 15,46 . Briefly, we obtained total whole–cell K + currents using a voltage jump to +50 mV, following a 500 ms prepulse of –125 mV.…”
Section: Fly Stocksmentioning
confidence: 99%
“…We isolated Shal currents by prepulse protocol, as previously described 15,46 . Briefly, we obtained total whole–cell K + currents using a voltage jump to +50 mV, following a 500 ms prepulse of –125 mV.…”
Section: Fly Stocksmentioning
confidence: 99%